Collaboration at a distance: from virtual teams to open source development - Cummings, Jonathon (Henry Stewart Talks, 2013)
Collaboration, Virtual teams, Geography, Space and time, Dispersion and technology, Time separation, Global development, Time zone span, Coordination problems, Task organization, Time allocation, Team performance, Open source development, Online community, Personal values, Work activities, Collaboration tools
Reviewed at 2020/04/30